Silencing the Subaltern in R. F. Kuang's Babel: A Spivakian Approach - Inti Nailis Syafa'ah (Journal of Language, Literature and Teaching, 2026)
The concept of subaltern and epistemic violence often featured in recent literary works, among others is R. F. Kuang’s Babel. This study uses the applications of Spivak’s subaltern theory in the historical fantasy novel Babel by R. F. Kuang through Victoire Desgraves and Letitia Price who are the main female characters of the story. Subaltern theory by Spivak most importantly addressed the difference of western feminist and subaltern women. Women can silence other women on account of their difference, such as class and race (Spivak, 1988). Using the postcolonial feminism framework, this study will use Babel by R. F. Kuang as the source of data. The researcher will analyse all the data that has been collected in several steps. First, the data will be analysed with Spivak’s theory of subaltern to uncover the representation of subaltern woman in Babel through Victoire Desgraves’ character. Second, the data will be analysed with Spivak’s theory of epistemic violence to prove Letitia Price’s action of trivialising Victoire Desgraves’ struggle as a subaltern. This study will contribute to offer understanding on how subaltern women can be silenced and harmed by invisible violence from western feminist who unconsciously disregard subaltern struggle.Keywords: Spivak, Epistemic Violence, Silence, Postcolonial Feminism, Babel